Analisis Pemasaran Buah Nanas (Ananas Comosus L Merr) di Desa Sarireja Kecamatan Jalancagak Kabupaten Subang - Ferry Firmansyah; Kuswarini Sulandjari; Suhaeni Suhaeni (Jurnal Ilmiah Wahana Pendidikan, 2021)
Pineapple is one of the horticultural plants that are very easy to cultivate in the tropics, including Indonesia, including in sarireja village, Jalancagak district, Subang Regency. The purpose of the research is to know the channels, functions and tasks of marketing, analyze farm revenues, profit marketing agencies, know the level of marketing efficiency of pineapple fruit. Method of determining farmer samples with Simple Random Sampling samples, traders / institutions involved (snowball sampling). Primary data was obtained through interviews using questionnaires, secondary data from the Ministry of Agriculture, Central Statistics Agency of West Java Province, Agriculture Office and Counseling Center. The data was analyzed with revenue analysis, farm R/C Ratio, profit, margin, farmer's share, and marketing efficiency. The results showed there are 2 (two) patterns of pineapple marketing channels, namely channel I (farmers-croupier-merchants retailers-consumers), channel II (farmers-merchants retailers-consumers). The marketing functions and duties of farmers conduct sales, harvesting, and distribution. croupier makes purchases, sales, harvesting, grading, distributing, risk insurers, conveying information, capital. Retailers make purchases, sales, grading, cleaning, risk insurers, bindings, and storage. Pineapple farming income Rp. 7.736.950/ha/16 months, R/C ratio 1.48 indicates the value of >1 which means it is worth trying. The profit of the institution on channel I farmers Rp. 2.550/kg, croupier Rp. 2.757,40/kg, retailers Rp. 2.088/kg, channel II farmers Rp. 4.787/kg, retailers Rp. 3.389/kg. Both marketing channels are efficient, but marketing channels II are more efficient with a margin of Rp. 4.000,-/kg, farmer's share of 55,56%, and marketing efficiency of 9,16%.